2019
DOI: 10.1002/pros.23929
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of human prostate carcinoma‐associated fibroblasts implicates a role for subpopulations in myeloid cell recruitment

Abstract: BackgroundCarcinoma–associated fibroblasts (CAF) are a heterogeneous group of cells within the tumor microenvironment (TME) that can promote tumorigenesis in the prostate. By understanding the mechanism(s) by which CAF contributes to tumor growth, new therapeutic targets for the management of this disease may be identified. These studies determined whether unique sub‐populations of human prostate CAF can be identified and functionally characterized.MethodsSingle‐cell RNA‐seq of primary human prostate CAF follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 47 publications
2
48
0
Order By: Relevance
“…In addition, laminin expression is reduced in the reactive stroma indicating disruption of the basement membrane [106]. Subsequent studies have given evidence of the pro-angiogenic and immunomodulatory properties of CAFs in prostate carcinogenesis [58,107]. Overall, the properties of CAFs and ECM components in prostate reactive stroma support the aforementioned idea that tumors behave as 'wounds that do not heal'.…”
Section: The Reactive Stroma In Prostate Cancermentioning
confidence: 88%
See 3 more Smart Citations
“…In addition, laminin expression is reduced in the reactive stroma indicating disruption of the basement membrane [106]. Subsequent studies have given evidence of the pro-angiogenic and immunomodulatory properties of CAFs in prostate carcinogenesis [58,107]. Overall, the properties of CAFs and ECM components in prostate reactive stroma support the aforementioned idea that tumors behave as 'wounds that do not heal'.…”
Section: The Reactive Stroma In Prostate Cancermentioning
confidence: 88%
“…Another example of CAF heterogeneity in PCa is the co-existence of CAF subpopulations that are positive/negative for TGFβ receptor II (TGFβRII), a feature that seems to promote prostate tumorigenesis [56,57]. Recently, single-cell RNA sequencing of human prostate CAFs has revealed six main CAF subpopulations that secrete different arrays of cytokines with various immunomodulatory properties [58]. Among these CAF clusters, the chemokines (C-C motif) ligand 2 (CCL2) and (C-X-C motif) ligand 12 (CXCL12) were found to be differentially expressed-information that could not be revealed by sequencing the RNA of the bulk population.…”
Section: Caf Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies described additional mechanisms of the recruitment of MDSCs by CAFs involving the CXCL1 chemokine, followed by differentiation by CXCL12, IL-6, vascular endothelial growth factor (VEGF) and macrophage colony-stimulating factor (M-CSF) [ 28 , 29 ]. A single-cell RNA sequencing study conducted in prostate cancer demonstrated that different clusters of CAFs secreted various levels of proinflammatory cytokines such as CXCL12 and CCL2, highlighting that several CAF subpopulations may interact with MDSCs [ 51 ].…”
Section: Cafs Constitute a Chemical Immune Barriermentioning
confidence: 99%